2018
DOI: 10.1177/1687814018773670
|View full text |Cite
|
Sign up to set email alerts
|

Plane-constraint-based calibration method for a galvanometric laser scanner

Abstract: Laser stripe vision sensors have limited application when the whole surface of an object has to be measured; therefore, a galvanometric laser scanner is presented using a one-mirror galvanometer element as its mechanical device to drive the light stripe to sweep along the object. A flexible plane-constraint together with a look-up table calibration algorithm by viewing a planar calibration target from unknown orientations is presented to calibrate the proposed galvanometric laser scanner. The plane-constraint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In the literature, much research has reported the calibration of galvanometric scanning systems. For instance, Mao et al [8] and Yang et al [9] reported the calibration of one-mirror galvanometric scanners, which were used in 3D measurement systems. Lüdtke et al [10] and Tu et al [11] calibrated two-mirror galvanometric laser scanners by using employed statistical learning methods (e.g., linear regression and artificial neural networks).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature, much research has reported the calibration of galvanometric scanning systems. For instance, Mao et al [8] and Yang et al [9] reported the calibration of one-mirror galvanometric scanners, which were used in 3D measurement systems. Lüdtke et al [10] and Tu et al [11] calibrated two-mirror galvanometric laser scanners by using employed statistical learning methods (e.g., linear regression and artificial neural networks).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar to the one-step calibration method, an invariance of cross-ratio (Zhou et al, 2005) or double cross-ratio (Wei et al, 2003) based approach is also employed to generate control points in two-step calibration method. Mao et al (2018) proposed a plane-constraint based calibration approach to effective and highly accurate extraction of much more control points for a structured light stripe vision sensor. There are also some methods that the 3D calibration target is constituted by a 2D calibration target and a movable platform (Li et al, 2008; Luo et al, 2014; Xie et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These laser scanners appear in several applications [28][29][30][31][32] due to their "good characteristics of high deflection speed, high positioning repeatability and concise structure" [25]. For the majority of the publications, the authors restrict their analysis to situations where a 2M-GLS measures a plane or a two-dimensional surface [33]. In such situations, there is no need to go beyond point-based calibrations.…”
Section: Introductionmentioning
confidence: 99%